B Bridging Generosity: A Study of Social Capital's Impact on Islamic Philanthropic Fundraising in Bandar Lampung - Yadi, Mulyadi; Jauhari, Tontowi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
The Islamic philanthropic fundraising by philanthropic institutions in Bandar Lampung is vital in supporting social, educational, health, and humanitarian programs. Even though several philanthropic institutions are actively involved in humanitarian activities and poverty alleviation, Bandar Lampung needs to fully optimize the potential for Islamic donations. This shows that there are interesting problems that are worth studying regarding fundraising by Islamic philanthropic institutions. This research aims to bridge the knowledge gap regarding the relationship between social capital and Islamic philanthropic fundraising, especially in Bandar Lampung, and the focus is to understand how social capital influences the success of Islamic philanthropic fundraising in this city. This research aims, among other things, to explain the factors that influence Islamic philanthropic fundraising and show the influence of social capital as a strategic tool in increasing community support for philanthropic programs. Research variables included Philanthropic Fundraising (Y), Trust (X1): Trust Level, Network (X2): Interconnection and Cooperation, and Institutionalization (X3): Organizational Structure and Norms. The data were collected from LAZNAS (Amil Zakat National Agency) donors in Bandar Lampung using Likert-scaled questionnaires and then analyzed using parametric statistics through SPSS version 22. The research results show a solid and positive relationship between trust, networks, institutionalization, and philanthropic fundraising. There is a significant correlation coefficient between these variables. The regression results show that trust, networks, and institutionalization positively influence philanthropic fundraising. Based on these findings, researchers recommend that Islamic philanthropic institutions, especially LAZNAS in Bandar Lampung City, comply with regulations and obtain government recognition, improve communication and transparency, professionalize fund management, develop networks and partnerships, and strengthen organizational structures and norms.